FAKTOR FAKTOR YANG MEMPENGARUHI TABUNGAN MUDHARABAH PADA BANK UMUM SYARIAH (BUS) DI INDONESIA TAHUN 2018 – 2019 - Nur Aini; Sri Isnowati; Agus Murdiyanto (Faculty of Economic and Business Universitas STIKUBANK, 2021)
This study aims to examine and analyze the factors that affect the amount of easy-to-use savings savings. Thesefactors are the Profit Sharing Rate, Liquidity, Bank Size and Number of Bank Offices. The object of this research is all Islamic Commercial Banks (BUS) that report their Financial Statements to the Monetary Services Authority, with an observation period for the first quarter of 2018 to the fourth quarter of 2019. The sampling method uses the Census method, namely the entire available population is sampled and there are 14 Sharia Commercial Banks. Data analysis using multiple linear regression. The results of the study found that the Profit Sharing Rate has no effect, Liquidity has a significant negative effect, while the Bank Size and Number of Bank Offices have a significant positive effect on the Total Mudharabah Deposits.